2023
DOI: 10.1088/1361-6463/acc25a
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional praseodymium-doped composite silica glasses for UV shielding and photonic applications

Abstract: Silica phosphate glasses strengthened with calcium oxide modifier and doped with different concentrations (0%, 0.5%, 1%, 1.5 mol%) of praseodymium (Pr3+) were synthesized by sol-gel method. The absence of sharp peaks in the x-ray diffraction (XRD) spectra confirms non-crystallinity of the glasses. Higher doping indicates increasing optical band gaps due to Burstein Moss shift, which also reflects on structural disorders at the absorption tails as validated by Urbach’s rule. The density increases with a subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 72 publications
2
2
0
Order By: Relevance
“…This is due to the partial phase changes in the glass materials, leading to two crystallization events [34], but noticeably diminutive for the identification of the phases. The intensity of the crystallization peaks (T p1 and T p2 ) is very small (<0.4 a.u), which conforms to the amorphous attribute of the glass systems observed in the x-ray diffraction structural analysis as previously reported [27].…”
Section: Thermal Analysis-tg-dscsupporting
confidence: 90%
See 2 more Smart Citations
“…This is due to the partial phase changes in the glass materials, leading to two crystallization events [34], but noticeably diminutive for the identification of the phases. The intensity of the crystallization peaks (T p1 and T p2 ) is very small (<0.4 a.u), which conforms to the amorphous attribute of the glass systems observed in the x-ray diffraction structural analysis as previously reported [27].…”
Section: Thermal Analysis-tg-dscsupporting
confidence: 90%
“…A similar tendency of the formation of non-bridging oxygen units and the associated defects, with the addition of dopants could be ascribed to the observed loss factor and the relaxation shift to higher frequencies, in the present system of glasses. This could be corroborated by the increase in the defects validated by Urbach energy up to 1 mol% of Pr 3+ in the glasses reported earlier [27]. However, the behavior deviates in the glass doped with 1.5 mol% of Pr 3+ and presents a largely suppressed trend in the loss.…”
Section: Dielectric Analysissupporting
confidence: 76%
See 1 more Smart Citation
“…The glasses were synthesized as per the scheme reported [6]. The raw materials, namely tetra ethoxy orthosilicate, triethyl phosphate, calcium nitrate tetrahydrate, and praseodymium nitrate hexahydrate, were stirred vigorously for 2 h and left for gelation and aging for the formation of glass monoliths.…”
Section: Methodsmentioning
confidence: 99%
“…The XRD diffraction patterns of all the synthesized glasses are shown in figure 1. XRD analysis of the samples revealed that the hydroxyapatite and tricalcium phases characteristic of the addition of calcium phosphate are absent, due to the larger molar ratio of silica added to the glass matrix [11,12]. The stereotypically sharp diffraction peaks resulting from the long-range ordering of lattices mark the crystalline attribute of a material.…”
Section: Characterization Techniquesmentioning
confidence: 99%